2021
DOI: 10.19184/bst.v9i1.19844
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Study of Phenylthiocarbamide (PTC) Taste Sensitivity In Population of The Osing in Kemiren Village-Banyuwangi

Abstract: The ability to taste phenylthiocarbamide (PTC), is autosomal trait inherited in a simple Mendelian recessive pattern. The frequency of Taster and non-Taster allele is varies in different populations. The purpose of the research is to investigate the prevalence, gene frequency and genotype frequency of taster (T) and non taster (ts of Osing population in Kemiren-Banyuwangi. PTC serial dilution method was used to assess the PTC Taster and non-Taster phenotypes. The Hardy–Weinberg method was used to determine all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…However, genetic variation changes will occur when there are disturbing factors such as mutations, environmental changes, random mating, and migration. 50,65 This study found that TNFSF13B rs9514828 gene polymorphisms were present in both patients with SLE with and without comorbid atherosclerosis. The frequency of the TNFSF13B rs9514828C>T polymorphism was noted to be higher in patients with SLE with atherosclerosis (66.67%) compared to those without atherosclerosis (42.86%).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, genetic variation changes will occur when there are disturbing factors such as mutations, environmental changes, random mating, and migration. 50,65 This study found that TNFSF13B rs9514828 gene polymorphisms were present in both patients with SLE with and without comorbid atherosclerosis. The frequency of the TNFSF13B rs9514828C>T polymorphism was noted to be higher in patients with SLE with atherosclerosis (66.67%) compared to those without atherosclerosis (42.86%).…”
Section: Discussionmentioning
confidence: 70%
“…26,29 The utilization of immunosuppressive and systemic steroid agents may potentially influence the comorbidities in patients with SLE. [48][49][50] Incidence of cardiovascular was significantly higher in patient with SLE. This study identified atherosclerosis as the primary comorbidity, followed by hypertension, hypercholesterolemia, obesity, and hyperglycemia.…”
Section: Discussionmentioning
confidence: 96%
“…Pemahaman rasa Phenylthiocarbamide (PTC) merupakan sifat yang dikendalikan secara genetic dan bervariasi dari suatu populasi ke populasi lain. PTC digunakan untuk melakukan mengamati variasi genetic atau keragaman genetic suatu populasi karena relative mudah dikerjakan, akurat, dan mampu menggambarkan sifat yang muncul dari sifat gen autosomal resesif yang dapat diwariskan (Alimba, 2010;Husain, 2013;Oktarianti, 2021). Senyawa PTC digunakan untuk mengetahui kapasitas sensor perasa pada lidah, dalam sekelompok orang atau populasi yang digolongkan sebagai tester dan non tester.…”
Section: Pendahuluanunclassified